Design and analysis of single pulse tests - El-Khatib, Noaman A.F. (Elsevier, 2011)
A procedure is developed for the design and analysis of single pulse tests. A new definition is adopted for the pressure response amplitude that eliminates the effect of pressure trend. The method is applicable for homogeneous reservoirs with negligible well bore storage and skin at both wells. The test may be performed in an interactive way. Analytical equations are derived that explicitly relate the dimensionless pulse time and dimensionless pressure response amplitude to the time lag ratio. This makes it possible to analyze the results automatically by a computer. Correlation charts are also presented for graphical analysis of test results. The charts are independent of the pulse ratio since it is not a parameter in the developed analytical equations. The time and pressure response amplitude are used to calculate the inter-well transmissibility kh/μ and storativity hϕct using graphical or analytical procedures. The effect of past production is also investigated. Past production is found to increase the estimated value of transmissibility but has little effect on the value of storativity.